40 W high beam quality Tm:YLF InnoSlab amplifier. (1st February 2023) - Gao, Jimeng; Long, Qunlong; Wang, Lei; Mao, Yefei; Xu, Zhaopeng
Abstract: We demonstrated a compact and excellent beam quality Tm:YLF InnoSlab amplifier at 1908 nm for the first time. The power of the seed laser was 10 W with beam quality factors of M 2 ⩽ 1.04. With the high-efficiency coupling of the pump light and the seed laser, the amplified power of 40.1 W was achieved under the pump power of 318.7 W without ASE. The beam quality factors M 2 were 1.07 and 1.37 in the vertical and horizontal directions, respectively. The RMS instability was measured to be less than 0.15% in 30 min. Meantime, we had established a general and simplified CW Tm:YLF laser amplifier model.